Justice & peace - Stoutzenberger, Joseph (Dubuque, IA : Brown-Roa, 2000)
[This book first] provides a foundation for a Catholic understanding of justice. [It next] examines key issues related to justice including: poverty in America, global poverty, sexual identity, marginalized groups, and stewardship. [Finally, the book] examines Catholic teaching on peace and current issues related to peace. -http://www.harcourtreligion.com.
Foundations for a just world: A just world, the Christian vision; Scripture, the God who takes sides; Church, the community that does justice; Guidelines for action, doing justice, living justly -- Issues of justice in our world: Poverty in America, a scandal we can overcome; Global poverty, making interdependence work; Sexual identity, women and men created in God's image; Race, beyond stereotypes to the American dream; Groups seeking justice, compassion for the marginalized; Earth justice, nurturing nature, our home -- Creating a peace-filled world: The challenge of peace, the Christian resolution of conflict; Peacemaking, a new attitude.
Includes bibliographical references and index.
Keywords: Christianity and justice -- Catholic Church -- Textbooks; Social justice -- Religious aspects -- Catholic Church -- Textbooks; Peace -- Religious aspects -- Catholic Church -- Textbooks; Christian education -- Textbooks for young people -- Catholic